Material behaviour law identification for the various zones of the spot-weld under quasi-static loadings. (1st January 2001) - Markiewicz, Eric; Ducrocq, Pierre; Drazetic, Pascal; Haugou, Gregory; Fourmentraux, Thierry; Berard, Jean Yves
The aim of this paper is to predict by FE simulation the non-linear behaviour and rupture of spot-welded assemblies subjected to quasi-static loadings and to show the feasibility of numerical works. The three material zones of the spot-weld (metal base, melted zone and heat affected zone) are analysed and studied on a metal sheet assembly structured 0.7/0.7mm Experimental works based on tensile-shear, cross-tensile and peeling tests are done, as well as a numerical sensitivity analysis on the three material zones. Different fracture modes are put into evidence. A methodology to identify the material behaviour law of the MB, HAZ and MZ is proposed. The rupture of the spot-welded structure is simulated with the help of the Gurson damage model. The damage parameters of the MB and HAZ are identified through an inverse method on the basis of tensile-shear and cross-tensile tests. The numerical/experimental comparison on the various applied quasi-static loadings validates this methodology.